Representasi Indonesia dalam Stand Up Comedy (Analisis Wacana Kritis Norman Fairclough dalam Pertunjukan Spesial Pandji Pragiwaksono “Mesakke Bangsaku”) - Angger Siswanto; Poppy Febriana (Universitas Muhammadiyah Sidoarjo, 2017)
The purpose of this research exposes the representation of Indonesia through a good comic material delivered by Pandji Pragiwaksono in a special performance